Optimization of Port Service Strategies Using The SWOT Method at PT. ASDP Indonesia Ferry (Case Study in Kolaka Regency) - Salwa, Nisrina (Yayasan Sinergi Kawula Muda, 2025)
This research investigates the strategic optimization of ferry port services at PT ASDP Indonesia Ferry in Kolaka using a SWOT based framework, particularly focusing on Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS). The study aims to assess how internal organizational strengths and external environmental pressures influence service performance. Employing a qualitative descriptive method, data were gathered through interviews, document analysis, and observational techniques, then synthesized using SWOT matrices to generate strategic insights. The IFAS findings indicate that factors such as employee motivation, leadership, process standardization, and digital integration are critical to internal efficiency. Conversely, the EFAS matrix identifies government regulatory support, competition from private operators, and environmental volatility as dominant external elements shaping service effectiveness. Notably, the study finds that cross functional collaboration and a culture of innovation are key determinants of resilience and adaptability. The results underscore the importance of aligning internal capabilities with external opportunities to strengthen strategic decision making. By highlighting the dynamic interplay between governance, technology, and policy environments, this study contributes to the literature on maritime service optimization and strategic public enterprise management.